16-28 Lincoln Street, ca. 1940 - Unknown (Tufts Archival Research Center, 2005)
Street-level view east-northeast of 16-28 Lincoln Street, located between Church Green to the east-northeast and Essex Street to the west-southwest. Signage adorns the facades of the buildings, which face northwest. Automobiles and large trucks are visible in the photograph. 5 3/8 x 3 1/16, 5 3/4 x 3 7/16 overall Photographs